Entrusted loans: a close look at China's shadow banking system - Allen,HF; Qian,Y; Tu,G; Yu,F (Journal of Financial Economics, 2019)
We perform transaction-level analyses of entrusted loans, one of the largest components of shadow banking in China. Entrusted loans involve firms with privileged access to cheap capital channeling funds to less privileged firms, and the increase when credit is tight. Nonaffiliated loans have much higher interest rates than both affiliated loans and official bank loans, and they largely flow into real estate. The pricing of entrusted loans, especially of nonaffiliated loans, incorporates fundamental and informational risks. Stock market reactions suggest that both affiliated and nonaffiliated loans are fairly compensated investments.